Optimisasi Systematic Layout Planning dan Perbandingan Work Sampling untuk Efisiensi Waktu Produksi di UD Cantenan - Dimas Hendarjati Pamungkas; Muhamad Samsul Huda; Roby Septiawan; Agung Joko Prasetya; Rizki Anugrah Robby; Ferida Yuamita (Politeknik Kampar, 2025)
This research aims to increase production efficiency at UD Cantenan, an aluminum metal manufacturing industry, through the application of the Systematic Layout Planning (SLP) method, the Kanban system, and Work Sampling productivity analysis. The initial layout shows the material movement distance between workstations is 41 m², with daily material handling costs reaching IDR 105,544. Through the SLP method, the layout was improved so that the moving distance was reduced to 37 m², and material handling costs fell to IDR 70,626 per day. The Kanban system was implemented to visually improve production flow, minimize waiting time, and reduce inventory buildup. Kanban implementation increased product delivery accuracy from 70% to 95%. Furthermore, productivity analysis using Work Sampling showed a non-productive activity ratio of 53% and productive activity reaching 65%. Normal production time measurements yield an average of 14 minutes per unit, indicating increased work efficiency. A total budget plan for implementing relayout of IDR 5,203,000 was also prepared as part of company resource management. The results of this research show that the combination of SLP, Kanban, and Work Sampling methods can significantly increase operational efficiency, optimize facility layout, and reduce production time and costs.